Odessa Recollected : the Port and the People. - Herlihy, Patricia (Biblioteka ukraïnoznavstva., 2019)
The present book brings together--indeed, re-collects--some of the most valuable and thought-provoking research on Odessa and its culture, community, and economy published by Patricia Herlihy over several decades of her work. Scholars of Ukraine, Russia, and the former Soviet Union will find in this book a helpful resource for their research and teaching.